A Decision Support System for smallholder campesino maize-cattle production systems of the Toluca Valley in Central Mexico. Part I—Integrating biological and socio-economic models into a holistic system - Castelán-Ortega, O.A.; Fawcett, R.H.; Arriaga-Jordán, C.; Herrero, Mario (Elsevier, 2003)
The objective of this work was to develop a Decision-Support System (DSS) in order to support the decision making process by campesino farmers of Central Mexico. Two biological models, one socio-economic model and a survey database form the DSS. The CERES-Maize model simulated the yield response of three local land-races of maize to different management systems. The second biological model, a cow model (dynamic hybrid model), was used to simulate alternative feeding systems. A multi-period mathematical programming model integrated the outputs of the previous models with the survey database. This model was used to find the optimal combination of resources and technologies that maximised farmers’ income. This model consists of 15,698 structural columns and 612 rows. The DSS successfully reproduced the functioning of the farming system's main components. More importantly, it simulated the complex interactions observed between the farmers and their crops and cattle, including traditional maize management practices.